Karakteristik Cyclic Voltammetry Katalis Platina-Titanium Dioksida Didukung Vulcan XC 72 - Reduced Graphene Oxide Dengan Variasi Perbandingan Massa - Putra, Dewa Made Dwi Adnyana; Joni, I Made; Suarda, Made; Astawa, Ketut; Sucipta, Made (Teknik Desain Mekanika, 2025)
Abstractt Proton exchange membrane fuel (PEMFC) cell is an electrochemical conversion technology that can produce electricity and heat by utilizing hydrogen energy. PEMFC has high efficiency, low operating temperature and has environmentally friendly properties so it strongly supports the use of green energy to be utilized in daily needs. This research focuses on optimizing the performance of PEMFC devices with platinum-titanium dioxide catalyst supported by Vulcan XC 72-reduced graphene oxide (Pt. TiO2/VC-rGO). This study used the modified hummer method, hydrothermal method and photodeposition method for the synthesis of Pt. TiO2/VC-rGO catalyst. The variation of VC and rGO used is mass variation, with the first variation 0.1 gr Pt: 0.1 gr TiO2 : 0.1 gr VC : 0.2 gr rGO, second 0.1 gr Pt : 0.1 gr TiO2 : 0.15 gr VC : 0.15 gr rGO, and third 0.1 gr Pt : 0.1 gr TiO2 : 0.2 gr VC : 0.1 gr rGO. with cyclic voltammetry (CV) testing, the results are not good in reading the electric current voltage in the three test samples. The third variation shows the widest range of oxidation and reduction reactions. Keywords: fuel cell, Catalyst, PEMFC, Pt/C, titanium dioxide, Synthesis,